Frozen fountain motif on window grille, Court View - Ayan Ghosh (2023)
Frozen fountain motif on window grille, Court View. The frozen fountain is a defining feature in Art Deco ornamentation in Mumbai and was introduced by architectural firm Merwanji Bana and Company. Their work is also notable for use of decorative stucco and glasswork on building facades.